Evaluating the feasibility of utilizing Gynocular-triage-to-diagnose application with VIA (Visual inspection with Acetic acid) in community cervical cancer screening programs in rural Mysore, India - Srinivas, Vijaya; Nishimura, Holly; Jayakrishna, Poornima; Krupp, Karl; Madhivanan, Purnima; Madhunapantula, SubbaRao (Indian journal of cancer, 2021)
Background: Cervical cancer is the third most common cancer among women in India. The aim of the study is to determine the feasibility of using the Gynocular-triage-to-diagnose (Gynocular T2D/GT2D) in conjunction with visual inspection with acetic acid (VIA) in community-based cervical cancer screening programs in rural Mysore, India. Methods: Between November 2015 and August 2016, the Public Health Research Institute of India (PHRII) implemented a mobile cervical cancer-screening in Mysore district using VIA and GT2D. Women underwent speculum exams and VIA positive cases were identified. Swede score was assessed using GT2D and a score >4 indicated further monitoring or referral for treatment. Papanicolaou (Pap) smears were conducted for selected cases. Statistical analysis was performed using Chi-square and Fisher's exact tests. Results: Among 199 women registered in the camp, 176 were included in the final analysis. 23 women were excluded due to vaginal bleeding. The average age of women was 39 years (range = 27-59 years). Among the 176 cases, 38 (21.6%) were VIA positive and 138 (78.4%) were VIA negative. Swede score of >4 was observed in 6 VIA positive and 7 VIA negative women. Two cases among VIA negative with a score of >4 were suggested biopsy. Conclusion: Gynocular triaging prevented overtreatment of 32 (18.1%) participants, and identified 7 subjects with >4 Swede score even in VIA negative cases, which would have been ignored if VIA alone was used. In summary, our study demonstrates that Gynocular triaging is feasible in community cervical cancer screening programs.